Cavity effect of synthetic jet actuators based on piezoelectric diaphragm - Dahalan, Md. Nizam (2012)
An active flow control technology known as synthetic jet actuator (SJA) is a zero-net mass-flux device to create pulsed jet that produces momentum to its surroundings and uses a vibrating diaphragm inside the cavity to generate an oscillatory flow through a small orifice. The performance of SJA depends on the design of an orifice and cavity, and oscillating membrane. SJA design based on piezoelectric diaphragm used in this project because of their size, lightweight, no need for external air supply, without the pipe complex, fast response time and low power consumption. This paper describes the cavity effect to SJA designs and experiments were performed to determine the air jet velocity produced through the orifice using a hot-wire anemometer at a different cavity thickness. The results demonstrate that the jet velocity increase would be better if the cavity thickness is reduced. However, more studies are needed to optimize the size of cavity and orifice for appropriate applications. © (2012) Trans Tech Publications, Switzerland.